The analysis of hazardous medical waste in dr. Soehadi Prijonegoro Hospital using a life cycle assessment approach - Adi, Bayu Kusuma; Joko, Tri; Setiani, Onny (Poltekkes Kemenkes Yogyakarta, 2023)
Hospitals are health services that produce waste and sources of pollution for human health and the environment. dr. Soehadi Prijonegoro Hospital produces the most medical waste in the Sragen regency and still needs cold storage. This research evaluated the management of hazardous toxicity material medical solid waste. Life cycle assessment calculations can be performed using a software application, Simparo 9.0. This scope of research with gate to gate approach. Inventory data was obtained from primary and secondary data collection. Daily medical waste is about 135 kg, while the average month is 3961 kg—medical waste management in dr. Soehadi Prijonegoro includes reducing, sorting, labeling, storage, transporting, and processing have been following applicable regulations. The results of the TCLP test of solids incinerator ash and chimney incinerator emissions meet the quality standards. The most significant impact on the ecosystem is the global warming potential in the emergency service room. For impacts, the natural resources and the impact on the ecosystem is the inpatient room due to excessive use of medical waste. Use of energy and materials to minimize emissions and waste.